Team-Based Evaluation of Extension Programs - Alexa J. Lamm; Amy Harder; Glenn D. Israel; David Diehl (EDIS)
Evaluation is essential for showcasing the public value of Extension programs. This 5-page fact sheet reports the evaluation skills and abilities expressed by county faculty during a survey in the fall of 2010 and offers strategies for enhancing evaluation efforts based on the strengths and weaknesses expressed in the survey. Written by Alexa J. Lamm, Amy Harder, Glenn D. Israel, and David Diehl, and published by the UF Department of Agricultural Education and Communication, August 2011. (Photo by Chuck Woods)